The Impacts of Ramadan Intermittent Fasting on Oxidant/Antioxidant Stress Biomarkers of Stable Chronic Obstructive Pulmonary Disease Male Patients. Issue 3 (3rd May 2019) - Mrad, Sawssan; Rejeb, Hadhemi; Ben Abdallah, Jihene; Graiet, Hajer; Ben Khelifa, Mouna; Abed, Amel; Ferchichi, Salima; Limem, Khelifa; Ben Saad, Helmi
No prior study has evaluated the impacts of Ramadan intermittent fasting (RIF) on oxidant/antioxidant stress (OS/AOS) biomarkers in patients with chronic obstructive pulmonary disease (COPD). The aim of this study was to assess the impacts of RIF on some OS/AOS biomarkers measured in male patients with stable COPD. Fifteen COPD patients (mean age: 71 ± 6 years) fasting Ramadan in 2017 volunteered to take part in the study. Three sessions (before Ramadan [BR], end Ramadan [ER], after Ramadan [AR]) were selected. Blood samples of OS (homocysteine [μmol/L], thiobarbituric acid reactive substances [TBARS, μmol/L]) and AOS (catalase [U/ml], ceruloplasmin [g/L], superoxide dismutase [SOD, ng/ml], zinc [µmol/L], albumin [g/L]) biomarkers were consistently taken 4.5 to 2.5 hr before the iftar . Findings were analyzed by applying Friedman or Kruskal–Wallis ANOVA. Comparisons of the number of patients with high OS [high homocysteine and/or TBARS] and low AOS (low catalase and/or ceruloplasmin and/or SOD and/or zinc and/or albumin) blood values between the three sessions were performed using the Cochran test. The median ± interquartile of homocysteine (BR: 21.48 [18.98–24.49], ER: 23.15 [21.77–26.45], AR: 24.87 [21.91–37.12]), ceruloplasmin (BR: 0.27 [0.24–0.30], ER: 0.28 [0.26–0.33], AR: 0.28 [0.25–0.32]), SOD (BR: 288.00 [112.00–400.00], ER: 182.00 [152.00–386.00], AR: 234.00 [190.00–420.00]) and the mean ± SD of TBARS (BR: 5.66 ± 1.26, ER: 4.59 ± 0.78, AR: 5.29 ± 1.69), catalase (BR: 120.97 ± 54.62, ER: 106.73 ± 50.92, AR: 137.39 ± 40.88), zinc (BR: 11.85 ± 2.01, ER: 12.47 ± 2.34, AR: 12.21 ± 2.58) and albumin (BR: 39.78 ± 3.19, ER: 40.74 ± 2.26, AR: 40.56 ± 2.38) were not significantly affected by RIF. The number of patients with high OS (BR [ n = 13], ER [ n = 15], AR [ n = 14]) or low AOS (BR [ n = 12], ER [ n = 13], AR [ n = 13]) statuses were not significantly influenced by RIF. In conclusion, RIF did not induce any significant statistical or clinical changes in OS/AOS biomarkers or statuses in COPD patients.